Law Under The Grip Of Power - Hutauruk, Appe (Jurnal Indonesia Sosial Sains, 2025)
The concept of the state of law is an idea that is considered the most ideal applied today in the context of a welfare state, although the concept is carried out with different perceptions and methods in each country in the world. The term "state of law" in Indonesian is often also translated as "rule of law" or "government based on law" in the sense that every behavior and policy of the government in making decisions must be based on the principle of legality and there should be no arbitrary actions that have the nuances of abuse of power and/or permeation of power. In the state of law, there is a strict restriction on the power of the government or the state that carries out the function of governance or state governance so as not to abuse power to oppress the people and amputate human rights as a basic right that is inherent in nature. In addition, so that the ruler's government as the dominant role holder does not give a special position to oligarchic groups that symbiosis manipulate law enforcement and undermine the democratic order to seize or maintain power hegemony. The essential principle in the state of law is that all people must be subject to the law equally based on the principles of equality and justice without discrimination. All people, both those who are ruled (people or citizens) and those who rule (rulers) in the interaction of the life of the nation and the state, are not immune to the law, in fact all without exception must submit and obey the applicable law according to the principle of equality before the law. The concept of the rule of law does not tolerate or even oppose totalitarian, dictatorial or fascist systems of government, nor against anarchist systems of government, which often treat the people arbitrarily in the name of power wrapped in the manipulation of law enforcement. In essence, the legal character produced in a democratic government under the concept of the state of law is responsive and accommodating. Likewise, the legal substance formulated in every law and regulation must reflect the recognition and respect for human rights. Human rights are one of the measures of law enforcement. But unfortunately the character of the law and the substance of the law in Indonesia are not realized at all because they are ignored by the rulers, in fact what happens is often that the law is applied according to the taste of the rulers, the principle of legality and the principle of equality before the law are only manipulative jargon because what happens in Indonesia is that the law is in the grip of power.